Body and Spirit in the Writings of Andrzej Towiański - Stanisz, Marek (Colloquia Litteraria, 2018)
Relationship between the body and the soul is one of the crucial issues that romantic anthropology, whose representatives included Andrzej Towiański, is concerned with. The founder of Koło Sprawy Bożej was convinced, just like other romanticists, that material world was subordinate to spiritual reality, as well as that the spirit unquestionably preceded over the body. Towiański underscored the key role that the body should play in one’s striving to achieve Christian perfection, which he believed to be a state of full maturity of a human being. According to Towiański, the body can only serve a man appropriately, when it is subject to the will of the spirit. Thus, the body should be appreciated and seen as a means to spiritual improvement and the entrance gate to a higher reality. On the one hand, this improvement should be achieved through offering a ‘three-fold Christian sacrifice’, recognising God’s intention in suffering that is being experienced and observing strict ethics in marital life, and on the other hand appreciation of bodily needs: cultural entertainment, proper fun and fitness.